Як підняття тарифів гальмує економіку - Яковенко, Р. В.; Yakovenko, R. (Газета „День”, 2019)
У статті визначено загальну економічну тенденцію: постійне підвищення цін на послуги підприємств житлово-комунального господарства та відсутність будь-якої обґрунтованості такої тенденції. Наведено наслідки такої тарифної політики. In the article has been determined the general economic trend that has taken place during the last 5 years: constant increase of prices for services of enterprises of housing and communal services and absence of any justification of such tendency. The consequences of such a tariff policy are presented.
Negative consequences of existing pricing tendencies in the sphere of utilities: theoretical and economic substantiation
Keywords: ціна; витрати; комунальні послуги; монополія; природна монополія; економічний цикл; price; expenses; utilities; monopoly; natural monopoly; business-cycle